NILAI KARAKTER DALAM LAWAK BALI â€œHAI PUJAâ€ - Ayu Suciartini, Ni Nyoman (Institut Hindu Dharma Negeri Denpasar, 2018)
The presence of parody or comedy in Bali using Balinese language can be an effective medium to instill the values of character to teenagers, especially millennial generation. The emergence of Balinese rhymes with the name ?Hai Puja? in social media is importantly appreciated as one of the media to instill the values of the characters because in parody, Hai Puja insert various moral messages in accordance with the times and easily accepted by the present generation. This study aims to describe the character values contained in every episode of Balinese poetry ?Hi Puja?. The theory used in this research is character education theory. This research uses descriptive qualitative design with assisted documentation method and questionnaire. The results of this study conclude that there is a character value contained in every joke uploaded on youtube by Hai Puja. Character values that arise include independent characters, hard work, discipline, respect, and tolerance. All of these character values are very effectively implanted and developed, especially for millenial generations that spend more time in cyberspace.